Aortic valve replacement in a systemic lupus erythematosus patient with aortic insufficiency - Denli, Şeyma; Ömeroğlu, Suat Nail; İpek, Gökhan and Göksedef, Deniz and Üreyen, Cenk and Sayılgan, Cem (Cerrahpaşa Medical Journal, 2014)
Systemic Lupus Erythematosus is associated with substantial morbidity and mortality if the patient has valvular heart disease. Aortic insufficiency was detected in a thirty-one year old man with Systemic Lupus Erythematosus nephritis and positive ANA on the 11th year of his corticosteroid treatment. The patient underwent aortic valve replacement and he was discharged without complications.